SPEECH ACT GENDER BASED (STUDY CASE: COMMENTATORS’ RESPONSES OF DONALD TRUMP SPEECH) - Siswana Siswana; Widi Sriyanto (Jurusan Sastra Indonesia, 2020)
This study aimed to describe the forms, attitudes, and typical speech acts of the illocutionary commentators by gender on President Donald Trump's speech at the Liberty University. The method used in this research was descriptive qualitative approach to speech acts. Data sources were obtained from commentators on President Donald Trump's speech. The data used was comments written below the speech video display downloaded on Youtube. The data analysis technique was an interactive analysis consisting of four stages, namely data collection, data reduction, data analysis, and drawing conclusions.